2021
DOI: 10.1186/s12906-021-03374-3
|View full text |Cite
|
Sign up to set email alerts
|

Bio-guided bioactive profiling and HPLC-DAD fingerprinting of Ukrainian saffron (Crocus sativus stigmas): moving from correlation toward causation

Abstract: Background Saffron or stigmas of Crocus sativus L. is one of the most valuable food products with interesting health-promoting properties. C. sativus has been widely used as a coloring and flavoring agent. Stigmas secondary metabolites showed potent cytotoxic effects in previous reports. Methods The present study investigated the chemical composition and the cytotoxic effect of Ukrainian saffron crude extracts and individual compounds against melan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…However, officially published data was not found, only oral reports. Our research (Mykhailenko et al, 2021a) has shown cytotoxic (MDA-MB-231 and IGR39 cells line) and neuraminidase inhibitory activities of saffron from Ukraine.…”
Section: Ethnopharmacological and Modern Clinical Application Of Saffronmentioning
confidence: 62%
“…However, officially published data was not found, only oral reports. Our research (Mykhailenko et al, 2021a) has shown cytotoxic (MDA-MB-231 and IGR39 cells line) and neuraminidase inhibitory activities of saffron from Ukraine.…”
Section: Ethnopharmacological and Modern Clinical Application Of Saffronmentioning
confidence: 62%
“…Flavonoids are potent antiproliferative and cytotoxic agents [ 37 ]. Their composition and concentration significantly contributed to the cytotoxic activity in Crocus extracts [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 29 ] These data also report the antioxidant properties of saffron by total phenolic content, radical scavenging activity, and ferric reducing antioxidant power in stigmas. [ 13,23,24,29 ] Thus, the published articles on saffron chemical composition are limited to several countries and the identification of mainly kaempferol and quercetin derivatives; the components quantitative content and their comparison are not everywhere, and the assessment of the influence of environmental factors is also given only for several countries. Various environmental factors, such as the geographical location of the plant at a different altitude, the amount of rainfall, seasonal variation, and different levels of exposure to sunlight, and in addition, the type of soil, have some influence on the phytochemical profile of plants.…”
Section: Introductionmentioning
confidence: 86%
“…[ 28 ] Previously, we found rutin, apigenin, caffeic acid, and ferulic acid in the stigma crude extracts of Crocus from Ukraine. [ 29 ] These data also report the antioxidant properties of saffron by total phenolic content, radical scavenging activity, and ferric reducing antioxidant power in stigmas. [ 13,23,24,29 ] Thus, the published articles on saffron chemical composition are limited to several countries and the identification of mainly kaempferol and quercetin derivatives; the components quantitative content and their comparison are not everywhere, and the assessment of the influence of environmental factors is also given only for several countries.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation